Yvon Delbos, le premier président du Groupe des Libéraux et Apparentés (1953-1956) - Berardi, Silvio (Studi Politici, 2025)
In June 1953, Yvon Delbos became President of the Libéraux et Apparentés Group. The primary aim of the essay is to reconstruct, mainly using archival sources, his political and diplomatic activities within the EU institutions. Delbos never understood liberalism in an abstract or conceptual form, but in an empirical, pragmatic dimension closely connected to political reality. From this perspective, the federal solution seemed to him the most congenial, to guarantee the full welfare of European civil society. He thus considered it to be a priority of his work to encourage not only a speedy democratization of the parliamentary institution, but above all to stimulate the attribution of new effective powers to this organism. Anti-communism animated all his institutional activity, as did the conviction of the necessary, as well as gradual, political and military integration of Western Europe. Durieux, therefore, felt himself to be a full European citizen and advocated the implementation of community policies aimed at the erosion of the nation-state dimension.